2023
DOI: 10.1007/s12281-023-00459-z
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis and the Impact of Azole-resistance

Abstract: Purpose of Review IA (invasive aspergillosis) caused by azole-resistant strains has been associated with higher clinical burden and mortality rates. We review the current epidemiology, diagnostic, and therapeutic strategies of this clinical entity, with a special focus on patients with hematologic malignancies. Recent Findings There is an increase of azole resistance in Aspergillus spp. worldwide, probably due to environmental pressure and the increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 141 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…Undoubtedly, one major factor that has accounted for treatment failure in these cases is the severe immunosuppressed status of the patients. Invasive aspergillosis after allogeneic transplantation of hematopoietic progenitors, further complicated by GVHD, has associated mortality rates of around 50–100% [ 15 , 41 ]. Remarkably, when the infection is caused by resistant isolates, the mortality noticeably increases [ 41 ], demonstrating that an efficient antifungal treatment is still valuable and can provide a measurable benefit in these patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, one major factor that has accounted for treatment failure in these cases is the severe immunosuppressed status of the patients. Invasive aspergillosis after allogeneic transplantation of hematopoietic progenitors, further complicated by GVHD, has associated mortality rates of around 50–100% [ 15 , 41 ]. Remarkably, when the infection is caused by resistant isolates, the mortality noticeably increases [ 41 ], demonstrating that an efficient antifungal treatment is still valuable and can provide a measurable benefit in these patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive and prolonged use of broad-spectrum azoles has significantly contributed to the widespread emergence of azole-resistant Aspergillus spp. These resistant strains have been linked to therapeutic failure and high mortality rates [ 62 , 63 ]. A single-center study reported that the prevalence of azole-resistant A. fumigatus among lung transplant patients was 17% [ 61 ].…”
Section: Culture Independent Diagnostic Assays For Invasive Aspergill...mentioning
confidence: 99%
“…diverse challenges it poses in contemporary management. Of particular concern is the emergence of azole-resistant Aspergillus fumigatus strains [1]. Several countries, especially the Netherlands and Denmark, have reported increasing rates of Aspergillus fumigatus strains.…”
Section: Introductionmentioning
confidence: 99%